Learning by watching Vernacular Iñupiaq-Inuit design learning as inspiration for design education - Janne Beate Reitan (Nordiskt Forum för Forskning och Utvecklingsarbete inom Utbildning i Slöjd (NordFo), 2014)
In this article, I explore a single case of vernacular clothing design — the practice and learning of design for contemporary Iñupiaq-Inuit clothing made by women from Kaktovik in Northern Alaska — and I hope to contribute to a better understanding of design practice and learning in general. Design research has many unexplored areas, and one of these omissions is vernacular design, or folk design. In my opinion, professional and academic design may well have something to learn from vernacular design, although this research is about vernacular learning and about what, why and how the ‘making’ discipline of clothing design is learned. This study was based on observations of and interviews with seamstresses and research-by-design, which includes authorial participation in designing and sewing in adherence to Iñupiaq tradition. All of this was recorded on digital video film. The investigation of Iñupiaq-Inuit clothing design indicates that watching was the most common way of learning, a phenomenon I have chosen to call learning-by-watching, a concept that can be seen as a development of both Schön and Wenger’s theories of learning, as influenced by John Dewey’s theory of learning-by-doing. This study will be discussed in connection with design education, from kindergarten to professional studies in higher education, in the forthcoming research project, Design Literacy, the purpose of which is to develop theory to improve design education in both compulsory and academic design education. Consequently, to improve design education in general, a thorough focus on learning-by-watching in communities of practice would make for more reflective practitioners and more sustainable design practices in the long run. Keywords: Vernacular design, clothing design, design thinking, learning-by-watching, learning-bydoing.